Management of Antithrombin Deficiency in Pregnancy - Hart, Christina; Rott, Hannelore; Heimerl, Susanne; Linnemann, Birgit (Hämostaseologie, 2022)
Antithrombin (AT) deficiency is a high-risk thrombophilia and a rare condition. The risk of venous thromboembolism (VTE) is increased in AT-deficient women during pregnancy and the postpartum period and is especially high in women with a prior history of VTE. A thorough assessment of VTE risk is recommended in pregnant AT-deficient women, comprising the degree and type of AT deficiency, genetic mutations, personal and family history, and additional preexisting or pregnancy-specific risk factors. Due to a lack of adequate study data, there is limited guidance on the management of AT deficiency in pregnancy, including the need for prophylactic anticoagulation, the appropriate dose of low-molecular-weight heparin (LMWH), and the role of AT substitution. LMWH is the medication of choice for the pharmacological prophylaxis and treatment of VTE in pregnancy. Patients with a history of VTE should receive full-dose LMWH during pregnancy and the postpartum period. AT concentrates are a treatment option when anticoagulation is withheld in potentially high-risk events such as childbirth, bleeding, or surgery and in cases of acute VTE despite the use of therapeutic dose anticoagulation. Women with AT deficiency should be counseled at specialized centers for coagulation disorders or vascular medicine, and close cooperation between obstetricians and anesthesiologists is warranted before delivery and during the peripartum period.
Keywords: antithrombin deficiency; heparin; anti-Xa monitoring; antithrombin concentrate; pregnancy